ФЕНОМЕН «COST DISEASE» СЕКТОРУ КРЕАТИВНИХ ІНДУСТРІЙ УКРАЇНИ - Kirzhetska, Mariia; Kirzhetskyy, Yuriy; Gaponiuk, Grigorii (Zhytomyr Ivan Franko State University, 2021)
The study of the analysis of the dynamics of indicators that characterize the current state of development of the creative industries sector of Ukraine was conducted to conclude the presence or absence of signs of "cost disease". The analysis was conducted at a high level of aggregation: distinguishing only two segments of the creative industries sector: cultural and creative. The study's relevance is that in a crisis in the economy, it is advisable to diagnose sectors that need support by attracting additional funding from the budget or private funds, as the losses that occur are long-term and difficult to compensate. The study aims to empirically verify the theoretical regularity of Baumol W.I., Bowen W.G. on the manifestation of signs of "cost disease" in the sector of creative industries of the economy of Ukraine based on available statistics. The study's methodology was to identify the symptoms of "cost disease" by comparing indicators of specific segments of the creative industries sector with indicators of macroeconomic dynamics. For this purpose, the time series of macroeconomic characteristics of the Ukrainian economy was used in work. Studies have shown the absence of signs of cost disease in the creative segment of the creative industries sector and the presence of two of the three signs in the cultural segment. In particular, the "lagging productivity" formed during the last five years has been revealed in the cultural segment. The second sign was also confirmed: "catching up" with wages, which is that wages in the cultural segment are growing faster than labour productivity in the diagnosed segment. Comparing the dynamics of the price index in the national economy and the cultural segment of the creative industries sector, we see that prices in the national economy grew faster than prices for services provided in the cultural segment of the creative industries sector. The third sign that indicates the presence of "cost disease" in the cultural segment - is missing. However, the specific income deficit in the cultural segment of the creative industries sector (which has a positive value due to one of the three signs of "cost disease") is offset by two other factors - "productivity lag" and "catching up" wage growth.